Characteristics of surface modified Ti-6Al-4V alloy by a series of YAG laser irradiation. (1st January 2018) - Zeng, Xian; Wang, Wenqin; Yamaguchi, Tomiko; Nishio, Kazumasa
Graphical abstract: Highlights: A double-layer Ti(C, N) film was synthesized on Ti6Al4V alloy by laser irradiation. The effect of laser irradiation pass upon microstructure and hardness was studied. The wear resistance of laser modified sample was improved by 37 times. The toxic V released from modified sample was less than un-treated Ti6Al4V in SBF. Results suggested potentiality of a new try to modify the Ti-based implant. Abstract: In this study, a double-layer Ti (C, N) film was successfully prepared on Ti-6Al-4V alloy by a series of YAG laser irradiation in nitrogen atmosphere, aiming at improving the wear resistance. The effects of laser irradiation pass upon surface chemical composition, microstructures and hardness were investigated. The results showed that the surface chemicals were independent from laser irradiation pass, which the up layer of film was a mixture of TiN and TiC0.3 N0.7, and the down layer was nitrogen-rich α-Ti. Both the surface roughness and hardness increased as raising the irradiation passes. However, surface deformation and cracks happened in the case above 3 passes' irradiation. The wear resistance of laser modified sample by 3 passes was improved approximately by 37 times compared to the as received substrate. Moreover, the cytotoxic V ion released from laser modified sample was less than that of as received Ti-6Al-4V alloy in SBF, suggesting the potentiality of a new try to modify the sliding part of Ti-based hard tissue implants in future biomedical application.